Proteomics: a tool for the study of plant response to abiotic stress (2011)
Due in part to human activity, changes in global climate behavior have manifested in an increase in extreme temperature related events such as drought, salinization, contamination and flooding of vast areas of the planet. Regarding agricultural activity, these uncertain climatic scenarios are likely to cause biotic and abiotic stress increases, which must be dealt with through science and technology. Holistic approaches, also known as “omics”: proteomics, genomics, transcriptomics, and metabolomics offer new ways of facing these coming climate changes. Proteomics provide a new approach to the identification of proteins of interest and to carry out a functional analysis of the genome and its relationship with the environment.New advances in proteomics include the use of highly efficient techniques such as bi-dimensional electrophoresis, multi-dimensional chromatography, mass spectrometry and second generation technologies for the analysis of polypeptides and proteins at tissue, organ, organelle and membrane levels, as well as bioinformatic tools. This review article is comprised of aspects related to the general model of stress in plants, and advances in proteomics which contribute to the understanding of water and salt stress in cereals of economic importance.